Enterprise Information Systems: 19th International Conference, ICEIS 2017, Porto, Portugal, April 26-29, 2017, Revised Selected Papers - Hammoudi, Slimane; Śmiałek, Michał; Camp, Olivier; Filipe, Joaquim (Lecture notes in business information processing, 2018)
This book constitutes extended and revised papers from the 19th International Conference on Enterprise Information Systems, ICEIS 2017, held in Porto, Portugal, in April 2017. The 28 papers presented in this volume were carefully reviewed and selected for inclusion in this book from a total of 318 submissions. They were organized in topical sections named: databases and information systems integration; artificial intelligence and decision support systems; information systems analysis and specification; software agents and internet computing; human-computer interaction; and enterprise architecture